Digitalization against the shadow economy: Evidence on the role of company size - Bálint Ván; Gábor Lovics; Csaba G. Tóth; Katalin Szőke (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2022)
Online cash registers (OCRs) are important tools for reducing the size of the shadow economy. This paper analyzes the impact on reported turnover and tax liability of introducing OCRs in Hungary using a fixed-effects panel and event study model. We identify strong size-related heterogeneity in the retail and the accommodation and food services sectors: smaller companies increased their reported turnover more than larger ones. Since large companies pay the dominant part of value-added tax, the effects on the payment of this tax were mitigated. We find significant spillover effects in both sectors, which are slightly stronger among larger companies.
Keywords: E26; H25; H26; 330; Value-Added Tax; Tax Evasion; Shadow Economy